Designing Persuasive Bin to Facilitate Waste Segregation in the Household Sector Through Design Thinking Application - Johanna Renny Octavia (Jurnal Sosioteknologi, 2023)
The increase in population causes an increase in the amount of public consumption, increasing the amount of waste. Based on databoks.katadata.co.id, households are known to be waste contributors. Then, based on the Katadata Insight Center (KIC) survey in 2019, it was found that 50.8% of households did not sort waste. The behavior of households is an important problem to be solved because mixed waste cannot be separated and recycled again. Seeing these conditions, it is necessary to design a waste bin to persuade households to perform waste-sorting activities. The waste problem is considered wicked, and design thinking is the appropriate method to approach it. Research with design thinking is carried out through understanding, observing, defining, creating ideas, prototyping, and testing stages. In testing the prototype, the persuasive level of the waste bin design was assessed using the Perceived Persuasiveness Questionnaire (PPQ). This research results in a waste bin consisting of four boxes equipped with an adjustable bulkhead, QR-Code, and removable sorting card that can make a sound when not throwing garbage